Is there a role for agricultural committees and stakeholder panels in improving information and accountability in extension service provision: Evidence from Malawi - Ragasa, Catherine; Mingote, Cristina Alvarez; McNamara, Paul E. (International Food Policy Research Institute, 2018)
This paper looks at village agriculture committees, model villages, and stakeholder panels at various levels as participatory and decentralized structures for improving demand articulation and accountability in agricultural extension service provision in Malawi. It uses various datasets including nationally representative household and community surveys, a survey of service providers, a survey of representatives from the various structures, focus group discussions, and key informant interviews. It employs various estimation methods including matching techniques, matching plus regression adjustments, and an instrumental variables approach.